Study guides

☆☆

Q: Evaluate 4xy - y when x equals 3 and y equals 2?

Write your answer...

Submit

Related questions

If x=3 and y=2, 4xy = 4(3)(2) = 12(2) = 24

If x=3 and y=-2, 4xy = 4(3)(-2) = 12(-2) = -24

4xy = 4(3)(-7) = - 84

2*3*4 = 24

1

5

(3 * 3)(2 * 5) (9)(10) 90

4xy+1=3y-7x 4xy-3y=-7x-1 y(4x-3)=-7x-1 y=(-7x-1)/(4x-3)

6 + 12 - 5 = 13

2xy*9 if x=3 and y = 2 2(3)(2)*9 12*9 108 You substitute x and y for their equivalent (3 and 2) then simply multiply 2*x*y, then multiply the answer of that by 9.

a=-2 4b=-2 --> b=-1/2 c=8 (-2)(-1/2)(8)(3)= 24

3x + 7 = 3(-3) + 7= -9 + 7= -2

(t-7)/w = (-3-7)/-2 = -10/-2 = +5 ( minus over minus = plus)

3 6

4xy + 6xz When factorising algebraic expressions treat them just as ordinary numbers. Ascertain what the common factors are. The factors of 4xy are 2 x 2 x 'x' x y The factors of 6xz are 2 x 3 x 'x' x z The factors common to both expressions are 2 and 'x'. Therefore, 4xy + 6xz = 2x(2y + 3z)

the difference between 2x2 +4xy-3 and x2-2xy-4 is?

(7 x 7) - (5 x 3)

2b + 3 b = 12 . 27 since the beginning is 2 x 12, which equals 24, and then you have to add the extra 3.

-1/3,1/3and 5/3

s(t) = 3t^2, t = 3 s s(3) = 3(3^2) s(3) = 27 units

(2x2+4xy-3)-(x2-2xy-4)Answer: x2+6x+1

2b=6squared, and 6x6=36

Take 3 and substitute into the expression given to you but not mentioned in the question here and evaluate the expression. "Sub and Solve" I say.

the answer is 5

5